1)Let "p(x)\\in \\mathbb R[x]" and "q(x)=p(x)+p(-x)" . We have "q(-x)=p(-x)+p(-(-x))=p(-x)+p(x)=q(x)" , so "q(x)\\in P(e)"
2)Check that "\\psi" is a linear map. Let "p(x)\\in \\mathbb R[x]", "q(x)\\in\\mathbb R[x]" and "\\alpha\\in\\mathbb R", then
"\\psi(p(x)+q(x))=\\frac{\\bigl(p(x)+q(x)\\bigr)+\\bigl(p(-x)+q(-x)\\bigr)}{2}="
"=\\frac{p(x)+p(-x)}{2}+\\frac{q(x)+q(-x)}{2}=\\psi(p(x))+\\psi(q(x))" and
"\\psi(\\alpha p(x))=\\frac{\\alpha p(x)+\\alpha p(-x)}{2}=\\alpha \\frac{p(x)+p(-x)}{2}=\\alpha\\psi(p(x))"
So "\\psi" is a linear map
3)Check that "\\psi^2=\\psi". Let "p(x)\\in \\mathbb R[x]", then
"\\psi^2(p(x))=\\psi\\bigl(\\psi(p(x))\\bigr)=\\frac{\\psi(p(x))+\\psi(p(-x))}{2}="
"=\\frac{\\frac{p(x)+p(-x)}{2}+\\frac{p(-x)+p(-(-x))}{2}}{2}=\\frac{p(x)+p(-x)}{2}=\\psi(p(x))"
So "\\psi^2=\\psi"
4)Let "p(x)\\in\\ker\\psi" , then "0=\\psi(p(x))=\\frac{p(x)+p(-x)}{2}" . We have "p(x)=-p(-x)", that is "p(x)" is an odd polynomial. So "\\ker\\psi" is the set of odd polynomials.
Comments
Leave a comment